2022
DOI: 10.1080/00325481.2022.2082805
|View full text |Cite
|
Sign up to set email alerts
|

The utility of neutrophil-to-lymphocyte ratio determined at initial diagnosis in predicting disease stage and discriminating between active and stable disease in patients with sarcoidosis: a cross-sectional study

Abstract: The utility of NLR determined at initial diagnosis in predicting disease stage and discriminating between active and stable disease in patients with sarcoidosis : Cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a recent study, it was shown that higher NLR values at the time of diagnosis were associated with a more advanced disease stage and an active clinical status in individuals with biopsy-proven sarcoidosis. A defined NLR cut-off value of ≥2.39 (with 72.0% sensitivity and 52.0% specificity) was established to effectively discriminate active from stable disease [118].…”
Section: Immune System and Sarcoidosismentioning
confidence: 99%
“…In a recent study, it was shown that higher NLR values at the time of diagnosis were associated with a more advanced disease stage and an active clinical status in individuals with biopsy-proven sarcoidosis. A defined NLR cut-off value of ≥2.39 (with 72.0% sensitivity and 52.0% specificity) was established to effectively discriminate active from stable disease [118].…”
Section: Immune System and Sarcoidosismentioning
confidence: 99%
“…On the contrary, Patterson and co-workers found a higher level of IL-5 and altered levels of IL-7 and GM-CSF in pulmonary fibrosis, supporting the transition hypothesis [ 65 ]. Recently, among 465 patients with biopsy-proven sarcoidosis, it has been shown the utility of neutrophil–lymphocyte ratio (NLR) in predicting advanced disease stage and discriminating between active and stable disease [ 66 ]. However further studies are needed to understand the role of the Th1/Th2 axis in developing fibrosis in patients with pulmonary sarcoidosis.…”
Section: T Cellsmentioning
confidence: 99%